My Home Quarantine on an App: A Qualitative Visual Analysis of Changes in Family Routines During the Covid-19 Pandemic in Chile - Vergara-Del Solar, A (Springer, 2023)
This article presents original findings from a longitudinal qualitative study on changes in individual and family life associated with safety and health measures implemented during the COVID-19 pandemic in three regions of Chile. We developed a methodological approach based on multimodal diaries in a mobile application, in which participants submitted photographs and texts to express changes in their daily lives under residential confinement. Content and semiotic visual analyses show a significant loss in instances of collective recreation, partially compensated through new personal and productive activities performed at home. Our results suggest that modal diaries serve as potential tools to capture people’s perceptions and meanings as their lives go through exceptional and traumatic times. We assert that using digital and mobile technologies in qualitative studies could allow subjects to actively participate in the co-construction of fieldwork and produce quality knowledge from their situated perspectives. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.